DAMPAK PEMBANGUNAN JALAN TOL TERHADAP FAKTOR SOSIAL, EKONOMI DAN LINGKUNGAN PADA USAHA BATIK DAN PERHOTELAN DI KOTA PEKALONGAN - Siswanto, Victorianus Aries; Wahjuningsih, Tri Pudji; Murtini, Murtini (JURNAL LITBANG KOTA PEKALONGAN, 2019)
The construction of the Trans Java toll road is a national program which is expected to have a positive impact on economic development for the Java region. Toll roads are built with the hope of reducing congestion as well as income of the state treasury. But on the other hand, the construction of this toll road raises new problems, namely reduced income, changes in the environment for batik traders, hotels, restaurants and other problems, because in the pantura area there are many small to medium-sized businesses that rely on business from visitors who pass through the northern coa st road. For this reason, with the construction of the Trans Java Toll Road, it is necessary to examine whether the construction of the Trans Java Toll Road has had an impact on economic, social and environmental changes. By using purposive sampling a samp le of 140 respondents was obtained. Respondents were drawn from batik businesses, batik consumers, hotels, hotel guests and the public. By using descriptive analysis the results of the study found that the greatest impact of toll road development is the economic impact. From questionnaire, 54.5% of batik businesses stated that their businesses had decreased and 72.7% of respondents from hotels stated that their room rent had decreased. Whereas from the elements of batik buyers, hotel guests and the public, the construction of this toll road has had a positive impact. Recommendations from the results of this study can be given that the Pekalongan City Government needs to hold national level events, need to hold religious tourism periodically, need improvemen t and promotion of Pekalongan tourism, it needs to be assessed if it is proposed to build a batik shop in a rest area, canting pillars or landmarks in the road to the Pekalongan toll exit as well as the batik businesses asking for real and immediate action from the government with this economic impact. Keywords: Trans java toll road, Toll road impact, Social factors, Economic factors and Environmental factors, Pekalongan city